DNA Barcoding and eDNA Metabarcoding for Identification Species: A Case Study (West Sumatra): DNA barcoding and eDNA metabarcoding - Roesma, Dewi Imelda; Tjong, Djong Hon; Syaifullah, Syaifullah; Nofrita, Nofrita; Janra, Muhammad Nazri; Aidil, Dyta Rabbani; Prawira, Furqan Dwiki Lintang; Salis, Viola Mutiara (Journal of Tropical Life Science, 2025)
The biodiversity of freshwater fish is important to study because there is data and information that remain undiscovered. The waters of Sumatra, especially West Sumatra, are areas with high freshwater fish diversity but have limited information. Providing information and genetic data has become one of the important things to conduct. DNA barcoding and eDNA metabarcoding have become molecular methods for identifying species and providing information about the presence of species in a region. A study using DNA barcoding and eDNA metabarcoding was conducted on freshwater fish in several locations in West Sumatra. Isolation and amplification of DNA were performed directly on individual samples and sequenced using conventional methods (Sanger sequencing) to generate DNA barcodes. Water samples were collected (2 liters) at each location using a sterile bottle. The water samples were filtrated, isolated, and amplified using universal primer and sequenced with next-generation sequencing techniques. The study successfully collected 25 species belonging to 14 genera, 2 families, and 1 order. A total of 134 sequences from West Sumatra with a length of 648-670 bp were analyzed. All DNA barcodes were submitted to the BOLD System and GenBank, NCBI. The mean Kimura two-parameter model (K2P) genetic distances within species, genera, families, and orders were 0.7%, 8.3%, 15.8%, and 21.3%, respectively. The eDNA metabarcoding technique has successfully detected three native fish species in the waters of West Sumatra (Barbonymus schwanefeldii, Mystacoleucus padangensis, and Rasbora jacobsoni). The availability of fish DNA barcodes in reference databases is crucial for the success of identification using eDNA metabarcoding. Combining identification using conventional methods and eDNA metabarcoding can provide more reliable results and become a reference for future freshwater monitoring.